2006
DOI: 10.1021/ac060031y
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic Protein Preconcentration Using a Simple Glass/Poly(dimethylsiloxane) Microfluidic Chip

Abstract: We discovered that a protein concentration device can be constructed using a simple one-layer fabrication process. Microfluidic half-channels are molded using standard procedures in PDMS; the PDMS layer is reversibly bonded to a glass base such as a microscope slide. The microfluidic channels are chevron-shaped, in mirror image orientation, with their apexes designed to pass within approximately 20 microm of each other, forming a thin-walled section between the channels. When an electric field is applied acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
195
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(200 citation statements)
references
References 34 publications
5
195
0
Order By: Relevance
“…One critical step for the nanochannel formation in PDMS chip is the generation of nanogaps, and several techniques have already been developed for this purpose. 21,22 In this work, we used Nafion film printing on the glass substrate to generate a submicron thick ion-selective membrane. 23,24 At first, SU8 photoresist (SU8-2025, MicroChem Inc., Newton, MA) was patterned on a silicon wafer to build a positive master.…”
Section: Microchip Fabricationmentioning
confidence: 99%
“…One critical step for the nanochannel formation in PDMS chip is the generation of nanogaps, and several techniques have already been developed for this purpose. 21,22 In this work, we used Nafion film printing on the glass substrate to generate a submicron thick ion-selective membrane. 23,24 At first, SU8 photoresist (SU8-2025, MicroChem Inc., Newton, MA) was patterned on a silicon wafer to build a positive master.…”
Section: Microchip Fabricationmentioning
confidence: 99%
“…Therefore, various online sample preconcentration techniques have been developed to improve the sensitivity of MCE. [6][7][8][9][10] One of the successful strategies is to combine other preconcentration devices with MCE on a single microchip, e.g., solid-phase extraction, 11 filtering using a nanopore or nanochannel, 12,13 and so on. 14,15 As a typical example, Kim et al reported that the preconcentration with a nanochannel could attain a million-fold improvement of the detectability, but it required a long analysis time of over 30 min.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 As a typical example, Kim et al reported that the preconcentration with a nanochannel could attain a million-fold improvement of the detectability, but it required a long analysis time of over 30 min. 13 Furthermore, the nano-fabrication schemes need an expensive apparatus and complicated procedures. Thus, it is appropriate for MCE to apply a rapid and simple preconcentration technique including field-amplified stacking (FASS), [16][17][18] sweeping, [19][20][21] transient isotachophoresis, 22,23 isoelectric focusing, 24,25 transient trapping, 26 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…3 In general, these devices use flow or electric field to manipulate biomolecules for specific purposes, including concentration, 4,5 separation, 6 and detection. 7 Most microfluidic devices in the literatures are prototypes to demonstrate new ideas.…”
Section: Introductionmentioning
confidence: 99%